ANALISIS BENTUK DAN FAKTOR PENYEBAB PERUBAHAN MAKNA PEYORASI DAN AMELIORASI DALAM BERITA KRIMINAL - Ketriyawati, Ketriyawati (Diksi, 2019)
(Title: Form Analysis and Factors That Cause Change in Peyoration and Amelioration Meanings in Criminal News). This study aims to analyze the changes in the meaning of peyoration and amelioration and the causes of changes in the meaning of peyoration and amelioration in the criminal news of the Radar Cirebon newspaper in the January 2019 edition. The research method used in this study is a qualitative method. Based on the data and results of the analysis, it can be concluded that the forms and changes in the meaning of the exploration and amelioration are in the form of words and phrases. Factors causing changes in the meaning of exploration and amelioration are factors of socio-cultural development, differences in usage fields, the existence of associations, and differences in responses. The results of the study can be used to develop class X Indonesian language subject matter in odd semseter with basic competence 3.15 analyzing aspects of meaning and language in biographies. In addition, research results can be a source of inspiration for journalists and journalists to be better in the selection and use of diction in writing criminal news. Hopefully, criminal news presented in the mass media, especially newspapers, is increasingly interesting by using variations in language and paying attention to the meaning contained there in.Keywords: change of meaning, exploration, amelioration, variety of journalism, criminal news